LATE-ONSET, BLEB-ASSOCIATED ENDOPHTHALMITIS CAUSED BY STAPHYLOCOCCUS AUREUS - Riskha Pangestika; Fifin Luthfia Rahmi; Maharani Maharani (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: Bleb-associated endophthalmitis (BAE) is a potentially sight-threatening complications of trabeculectomy and is associated with poor visual outcome. BAE denotes an ocular infection with involvement of the vitreous, which usually develops months or years after glaucoma filtering surgery. The purpose of this case report was to present a case about late onset BAE caused by Staphylococcus aureus. Methods: A 55-year-old male presented with a 3-days history of left eye pain, redness, hypopion decreased visual acuity and hypotony with Seidel test positive. He had a history of primary open angle glaucoma that was treated with a combined procedure of cataract surgery and trabeculectomy in the left eye ten years earlier. His visual acuity had decreased from 6/20 to light perception. This patient showed signs of hypotony, endophthalmitis, leak, and pain but no previous history of using anti-fibrotic agents. BAE causative organisms cultures grew the S.aureus, that frequent cause of acute-onset endophthalmitis. The patient underwent treatment with pars plana vitrectomy, vitreous taps, administered intravitreal antibiotic, and prescribed hourly topical antibiotic. Six months after his last treatment, his left eye shows no residual infection, and visual acuity increase to 1/60. Results: One case of late onset BAE with visual improvement after early vitrectomy, intravitreal, oral and topical antibiotic treatment. Conclusion: Despite the poor prognosis of BAE caused by S.aureus infection, after proper treatment can yield an adequate result, as demonstrated in this case.